MONTE CARLO NEUTRON DOSE MEASUREMENT IN PROTON THERAPY FOR HEALTHCARE WORKER RADIATION SAFETY - Hadi Lesmana; Wahyu Setia Budi; Rasito Rasito; Pandji Triadyaksa (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: Proton therapy is an innovative and highly advanced external radiation therapy modality for cancer treatment that uses positively charged atomic particles. The usage of proton therapy facilities in Asia has been increasing and will be followed by Indonesia in the short-coming years. In line with its significant benefits, the application of proton therapy also requires radiation protection awareness due to its higher energy used by protons produces scattered photon and neutron radiation in proton interactions. Therefore, optimal verification is needed in the commissioning process for designing proton therapy shielding bunkers. Objective: This research aims to examine the effect of concrete density on proton shielding by calculating the equivalent dose H*(10) of neutrons in the treatment control room (TCR) and the door of the compact proton therapy facility (CPTC) using Particle and Heavy Ion Transport code System (PHITS) simulation software. Method: The proton facility modeled for this simulation uses a compact proton therapy type planned to be built at one of the radiotherapy facilities in Indonesia. The proton therapy bunker model consists of a synchrocyclotron accelerator room and an examination room with standard configurations, wall thicknesses, and modeling areas under compact proton therapy standards. The analysis is focused on assessing the suitability of concrete materials and wall thicknesses and determining the neutron exposure dose values in the TCR and CPTC doors. The geometry, radiation source, and type of concrete in the wall are simulated from a conservative assumption to a more realistic model. Result: At the designated points in the TCR and CPTC door, measurements are taken from the simulation, which indicates that the equivalent dose H*(10) value is below one mSv/year. Conclusion: This value indicates that the dose rate passing through the wall does not exceed the dose limit value already set at one mSv/year for the general public.